The Application of Physical Modelling Techniques to Problems in Tunnelling - Wold M; Enever J; Walton R (The Australasian Institute of Mining and Metallurgy, 1976)
Photoelastic and equivalent material model ling techniques for studying stresses and defor- mations and modes of failure in geological and engineering structures are described. The appli- cation of these techniques to the solution of tunnelling design problems is outlined. Models may contain heterogeneous components to simulate geological and man-made structures and may be two- or three-dimensional. Prototype construc- tion procedures and time dependent behaviour may be modelled. Examples of recent model studies carried out for the design of underground railway tunnels are given. Development of photoelastic and equi- valent material modelling techniques and facili- ties at the CSIRO, Division of Applied Geomech- anics are described, including a biaxial and triaxial frame for testing large scale two and three dimensional equivalent material models and components of full scale prototype structures.